DETERMINANTS OF NON-MUSLIM CREATIVE ENTREPRENEURS' INTERESTS APPLYING FINANCING AT SHARIA BANK - Soelistyo, Aris (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
Islamic banks operated based on Islamic principles and were more affected by the Covid-19 pandemic than conventional banks because of their higher fee structure. However, to restore the economy, more and more non-Muslim entrepreneurs are applying for business financing at Islamic banks. This study aimed to determine the factors that strongly influence the interest of non-Muslim creative entrepreneurs in Malang to apply for financing at Islamic banks. Using a sample of 112 creative entrepreneurs selected by accidental purposive sampling, the quantitative data obtained from distributing the questionnaires was finally analyzed using PLS-SEM high-level analysis. The study's results divulged four strong factors that influence the interest of non-Muslim creative entrepreneurs in applying for financing at Islamic banks: social influence, reputation, promotion, and services. In contrast, the other four factors did not have a strong effect. Future research is expected to consider the type of financing selected as a control variable.